Biofabrication of an Esophageal Tissue Construct from a Polymer Blend Using 3D Extrusion‐Based Printing. Issue 9 (28th March 2022) - Farhat, Wissam; Ayollo, Dmitry; Arakelian, Lousineh; Thierry, Briac; Mazari-Arrighi, Elsa; Caputo, Valentino; Faivre, Lionel; Cattan, Pierre; Larghero, Jérôme; Chatelain, Francois; Fuchs, Alexandra
Abstract : Many tissue engineering approaches are being explored to offer solutions for diseased esophageal tissue and its repair. However, classical techniques in tissue engineering are not capable of recapitulating the structural and functional parameters of native esophagi. Esophageal 3D bioprinting is yet an emerging field but holds great promise in meeting this challenge. Herein, the use of extrusion‐based 3D printing is examined to generate esophageal substitutes from a polymer blend‐based formulation. The fabricated 3D esophageal structures are printed at a very high speed without collapse and without the use of supporting material. In vitro analysis reveals that the printed material enables cell adhesion, proliferation, and migration into the deeper zones. Moreover, the designed construct is suturable to the native esophagus and exhibits no leakage while offering mechanical properties similar to that of the native tissue. Overall, these biochemical and biomechanical features make the reported artificial esophagus a promising solution for the repair of damaged esophagi. Abstract : An esophageal substitute 3D printed from a blend of natural and synthetic polymers shows excellent performance in mimicking the properties of the native organ, and exhibits no leaks when sutured to a native esophagus. It also allows cell invasion and slow degradation in vitro making it a promising solution for the repair of damaged esophagi.